Validity Test of The Results of The Development of Pedagogical Competence Training of Lecturers Based on Action-Based Learning in Colleges - Syoviana, Elvi; ., Rusdinal; ., Hadiyanto; Nurhizrah Gistituati; Marsidin, Sufyarma (Journal of Ecohumanism, 2024)
This research aims to clarify the validity of developing a model for the training of pedagogical competence of lecturers in Islamic religious colleges. This study uses the research development method—subjects of research as many as 23 colleges in West Sumatra. The research model uses the ADDIE research model with development stages. The results of the study showed that the results of the validity test derived from the results of the validator against the Development of Competency Training of Lecturers based on Action-based Learning in Colleges were declared valid on each validity test result of the interclass correlation coefficient of the product results, i.e. model book (0.910), material book (0.909), instructor book (0.926), participant manual (0.925). The interclass correlation coefficient of the product is categorized as very high and is effectively used because the interclass correlation coefficient scores in the range of 0.81 to 1.00. The value of the interclass correlation coefficient of the product results based on the validity test results on the development of the competency training of lecturers based on action-based Learning in colleges is stated to have a high level of validity so that it can be used. The results of the validity test are tested for their feasibility so that the results of the product can be used to implement action-based learning-based lecturer competence training in colleges